TRANSFER OF EMPLOYEES AS A MEASURE TO ADDRESS COLLECTIVE REDUNDANCY - Radovanović, Jelena (Glasnik Advokatske komore Vojvodine, 2025)
ABSTRACT: Collective redundancy is an ever-present problem in many sectors and organizations, especially at a time when technology and automation are changing the way the labor market functions. This issue is not only a challenge for individuals who lose their jobs, but also for companies, communities and society as a whole. There are many reasons for redundancy. Technological advances often replace labor with machines and software, thus reducing the need for manual workers. Also, globalization allows companies to move production to countries where labor costs are lower. In addition, inefficient organization of work within the company or economic crisis can lead to a certain number of employees becoming redundant. The consequences of this situation are profound, because individuals who lose their jobs face financial problems, and at the same time, society is faced with the growth of unemployment, which can lead to an increase in poverty, social tensions and a decrease in overall economic activity. One of the key solutions is moving the employee to another workplace, which is what this paper will deal with. Transfer to another workplace is one of the key measures used to improve employment and efficient human resources management, which avoids the collective dismissal of all employees. This practice enables employees to move from one workplace to another, within the same organization or even within a wider system, with the aim of solving the problem of surplus labor, filling deficit positions and optimizing work processes. Therefore, this article will analyze precisely the transfer of an employee to another workplace, as a measure to solve the excess of employees, with reference to problems in practice.